Upstream and Downstream – Exciting Advances to Modernize Fish Passage and Improve Data Collection. Issue 10 (30th September 2021) - Grasty, Sarah; Messina, Michael; Bryan, Janine
Abstract : Considering the myriad of ways in which advanced technology is being used in fisheries research, keeping atop of the newest developments is a challenge. The transfer of such specialized knowledge, even within the fisheries community, can be difficult, thereby hindering more widespread use of advanced technology in fisheries research. This predicament can be further compounded when information exchange between the freshwater and marine fisheries communities is limited. In a constantly shifting technological landscape, effecting stronger information transfer about technology within the fisheries community will lead to greater innovation, broader application, and more efficient and accurate science. This is the goal of the AFS Fisheries Information and Technology Section (FITS). This is the third article in a series that FITS has coordinated with Fisheries to highlight some of the ways in which the latest advanced technologies are being used in marine and freshwater fisheries research. To learn more, check out https://units.fisheries.org/fits/, find us on Facebook and Twitter (@AFSFITS).